On the geometric trinity of gravity, non-relativistic limits, and Maxwell gravitation - March, E; Wolf, W; Read, J (LSE Press, 2024)
We show that the dynamical common core of the recently-discovered non-relativistic geometric trinity of gravity is Maxwell gravitation. Moreover, we explain why no analogous distinct dynamical common core exists in the case of the better-known relativistic geometric trinity of gravity.